“I Want to Be a Forensic Scientist Playboy Bunny” - Waldner, Lisa Marie (Auckland University of Technology, 2013)
The moving image work I want to be a forensic scientist playboy bunny offers a creative consideration of contemporary female representation. This thesis considers how a typographic discourse might communicate the current complexities and contradictions inherent in the lived lives of young New Zealand women. These lives navigate a culture dominated by a postfeminist sensibility that is manufactured and reinforced throughout popular media.
Keywords: Feminism; Consumerism; Postfeminism; Commodity feminism; Consumer culture; Popular culture; Kinetic typography; Animated typography; Animated type; Spatio temporal type; New Zealand women; Postfeminist